Effect of Mulch Application and Different dates of Transplanting under Low Tunnel on Growth, Yield and Economics of Chilli (Capsicum annuum L.) - Tejpreet Kaur1, Kulbir Singh, S. K. Jindal, S. S. Walia; Dilpreet Talwar (Indian Journal of Extension Education, 2018)
The present investigation was conducted for two consecutive years i.e. 2016-17 and 2017-18 at Department of Vegetable Science, Punjab Agricultural University, Ludhianato study the effect of mulching and date of transplanting under low tunnel on plant microclimate and growth. Plant height and number of branches were observed maximum in treatments that were transplanted on 15th December under polythene mulch black, however, plots that were mulched with black polythene and transplanted on 15th February took least number of days to reach 50% flowering. Yield parameters (number of fruits plant-1, fruit yield g plant-1 and total fruit yield q ha-1) were maximum with application of polythene mulch black and transplanted on 30th November and was statistically at par with 15th December transplanting which might be due to longer crop duration. Early crop and higher yields results in obtaining more net returns, thus, economically proving feasible option for farmers.Therefore, transplanting on 30th November and 15th December under black polythene mulch could be beneficial for obtaining early yield and higher returns.